Microprocessor implementation of three phase PWM switching strategies - Mekhilef, Saad; Rahim, N.A.; Omar, A.M. (IEEE, 1999)
This paper presents a theoretical analysis and practical implementation of the natural and regular (symmetric, asymmetric) sampled three-phase PWM waveform, which was digitally implemented on a microprocessor, and the essential considerations involved in the feasibility of using a microprocessor software-based calculation to generate PWM. All the necessary microprocessor hardware/software techniques and algorithms required to implement and generate three-phase Pulse Width Modulation (PWM) are developed in detail, and demonstrated using practical results from an experimental microprocessor board. The techniques developed and presented in this paper are readily applicable to other currently available microprocessors, with minor modifications to reflect the special features of the particular microprocessor used. Particular emphasis has been placed on the basic concepts and principles, rather than concentrating on the details of a particular microprocessor.